Prevalence and characterization of rotavirus from faecal samples of children and animals* - KUMAR, MANISH; BHILEGAONKAR, K N; AGARWAL, R K (The Indian Journal of Animal Sciences, 2011)
Faecal samples (147; 60 bovine calf, 40 children, 47 piglets and pigs) were screened for the presence of rotavirus by RNA-PAGE and RT-PCR. The RT-PCR assay was standardized for the bovine and human rotavirus to amplify VP7 gene of the group A rotavirus. Out of 147 samples, 40 (27.2%) were found positive for rotavirus by RNA-PAGE, whereas only 15 turned out positive by RT-PCR. In bovine calves 21 (35%) and in children 19 (47.5%) cases were positive for rotaviral presence by RNA PAGE, on the contrary, RT-PCR was able to detect 7 cases of bovine (11.66%) and 8 cases of human (20%). We also showed G10 genotyping of rotavirus isolates of bovine origin by PCR. All the samples turned out to be PCR positive indicating that G10 is a predominant genotype responsible for bovine rotaviral diarrhoea in and around Bareilly region. The results indicated that direct detection of rotavirus by RT-PCR from faecal sample was not satisfactory as compared to RNA PAGE, probably due to large product size and sequence variations in rotaviruses.